Analisis Pengaruh Kualitas Layanan dan Strategi Harga terhadap Kepuasan, serta Dampaknya terhadap Loyalitas Jamaah Umroh Sawita Group, Jakarta - Firdaus, Ferry; Rochman, Fatchur (Universitas Brawijaya, Indonesia, 2012)
this research aims to analyze the effect of service quality and pricing strategy on satisfaction, and its impact on loyalty of Umrah Sawitha Group is customers. Data are analyzed descriptively and inferentialyby using PLS, wich is smart PLS version 1.10. Data are obtained by survey on members of Umrah Sawitha Group who were departed in 2011 and 2012, for to 189 respondents the analysis result proves that service quality has positive and significant effect on group members'satisfaction. Pricing strategy has positive and significant effect on satisfaction and loyality. Nevertheless, satisfaction does not home any positive influence on members'loyalty.